استخدام طريقة Shift-Share Analysis لتحليل مكونات التغير الاستثماري والقوة العاملة في سورية خلال الفترة 1994-2005. (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يُعدُّ تحقيق التوازن التنموي على صعيد القوى العاملة بصورة عامة، والمشتغلين بصفة خاصة، من أهم الأهداف التي تسعى إليها السياسات الاستثمارية وسياسات التشغيل في اقتصاديات العديد من دول العالم، إذ تقوم الاستثمارات على تحقيق التوازن المكاني والنوعي للقوى العاملة من خلال التنافس والتشارك في تأمين فرص العمل وتطويرها. و يُعدُّ تحليل مكونات نمو المشتغلين وتفصيلاته، ومن ثَمَّ التنافسية والتشاركية بين القطاعات الاقتصادية المختلفة، من أهم الأسباب المساعدة على إيجاد وخلق فرص العمل. لذلك اعتمدنا في دراستنا هذه على إيضاح النمو التشاركي والتنافسي لبيانات القوى العاملة في سورية وفق طريقة مكونات المزج الاستثماري بإتباع طريقة SHIFT-SHARE ANALYISIS (SSA)، ثم دراسة مكونات التغير الاستثماري للفترة 1994-2005، وللفترة 2005-2006 بالاعتماد على بيانات القوى العاملة للفترة السابقة، وعلى بعض بنود الخطة الخمسية العاشرة في سورية. Achieving the developmental balance concerning workforce, in general, and the employees, in particular, is one of the most important goals the investment studies and employing policies aim to achieve in many countries. The investments are designed to achieve the balance both in place and quality of the workforce through competition and corporation among them to create and improve job opportunities. The analysis of the constituencies of employees growth and its details as well as the competition and corporation among the different economic sectors, is one of the most important reasons for creating job opportunities. So we focused in this study on explaining the development of workforce’s competition and corporation in Syria as the workforce data based on investment strategy of  SSA during 1994-2005, and 2005-2006 depending on the data of the work force for the mentioned period and on some articles of the Tenth 5-year –plan in Syria.